EXPERIMENTAL STUDY ON THE INJECTION CHARACTERISTICS OF HYDROTREATED VEGETABLE OIL IN A DIESEL ENGINE COMMON RAIL SYSTEM - VÕ TẤN CHÂU; DUONG HOANG LONG; CHINDA CHAROENPHONPHANICH (Journal of Science and Technology - IUH, 2022)
The diesel combustion is primarily controlled by the fuel injection process. The start of injection therefore has a significant effect in the engine, which relates large amount of injected fuel at the beginning of injection to produces a strong burst of combustion with a high local temperature and high NOx formation. This paper investigated the impact of Hydrotreated Vegetable Oil (HVO) and blends of 10%, 20%, 30%, 50%, 80% by mass of HVO with commercial diesel fuel (mixed 7% FAME-B7) to injection process under the Zeuch’s method and compared to that of B7. The focus was on the injection flow rate in the variation of injection pressures, back pressures, and energizing times. The experimental results indicated that injection delay was inversely correlated to HVO fraction in the blend as well as injection pressure. At different injection pressures, HVO revealed a slightly lower injection rate than diesel that resulted in smaller injection quantity. Discharge coefficient was recognized larger with HVO and its blends. At 0.5ms of energizing time, injection rate profile displayed the incompletely opening of needle. Insignificant difference in injection rate was observed as increasing of back pressure.
Keywords: Biodiesel Production and Applications; Vehicle emissions and performance